1985
DOI: 10.1016/0014-5793(85)80007-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that biosynthesis of platelet‐activating factor (paf‐acether) by human neutrophils occurs in an intracellular membrane

Abstract: Human polymorphonuclear leukocytes (PMN) were incubated in the absence or presence of the calcium ionophore A23187 (6 PM) for 10 min at 37°C. They were then lysed by nitrogen cavitation and fractionated using Percoll gradients. Three major fractions of increasing density corresponding to plasma membrane, intracellular membranes and secretory granules were detected using [3H]concanavalin A, NADH-dehydrogenase and /?-D-glucuronidase as respective markers. In both cases, the acetyltransferase activity responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

1987
1987
2002
2002

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 20 publications
0
18
0
4
Order By: Relevance
“…Our findings lead us to conclude that protein kinase C does not activate the acetyltransferase in intact neutrophils. The findings fit a model in which both cPLA2 (30,32) and acetyltransferase are activated in concert by the p38 kinase cascade in response to TNF-␣ and other cytokines.…”
Section: Table Imentioning
confidence: 74%
See 1 more Smart Citation
“…Our findings lead us to conclude that protein kinase C does not activate the acetyltransferase in intact neutrophils. The findings fit a model in which both cPLA2 (30,32) and acetyltransferase are activated in concert by the p38 kinase cascade in response to TNF-␣ and other cytokines.…”
Section: Table Imentioning
confidence: 74%
“…We employed microsomes from unstimulated cells as our acetyltransferase source and evaluated the effect of various recombinant, constitutively activated MAP kinases on acetyltransferase activity. It has been recognized for some time that the acetyltransferase is localized in an internal membrane source (32,33), and although the compartment has not been unequivocally determined, it has been suggested that it resides in either the tertiary granule or endoplasmic reticulum membranes (34). Regardless of the exact source, microsomal fractions were found to contain the highest specific activity of acetyltransferase activity.…”
Section: Activation Of Map Kinase(s) and Acetyltransferase By Tnf-␣ mentioning
confidence: 89%
“…Human ECs do not appear to use the DTT-insensitive cholinephosphotransferase pathway (Blank et al, 1986;Bussolino, 1987a), but instead synthesize PAF in a two-step reaction in which a phospholipid precursor, 1-O-alkyl-2-acyl-sn-glycero-3-phosphocholine, is hydrolyzed by a phospholipase A2 yielding 1-O-alkyl-snglycero-3-phosphocholine, which is then acetylated at the sn-2 position by an acetyltransferase to yield PAF (Prescott et al, 1984;Whatley et al, 1989). Although we cannot exclude the possibility that PAF is synthesized in the plasma membrane, we assume that the major site of PAF synthesis in ECs is the endoplasmic reticulum based on the location of phospholipid synthesis in mammalian cells (Bishop and Bell, 1988), and the localization of PAF acetyltransferase in microsomes from several cells and tissues (Ribbes et al, 1985;Snyder, 1987;Mollinedo et al, 1988). In human PMNs, both PLA2 and acetyltransferase activities are found in intracellular organdies; the acetyltransferase is localized in microsomal and granular fractions (Mollinedo et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Cells (lO'/ml in 137 mM NaCl, 2.7 mM KCl, 5.5 mM glucose, 20 mM Hepes, pH 7.4) were isolated on Percoll [16,17]. Cells were then incubated for 15 min at 37°C with ['H]PAF (7-14 nM, 1 ,&i/10' cells) and washed twice with Hepes buffer containing 2.5% (w/v) bovine serum albumin.…”
Section: Cell Incubationmentioning
confidence: 99%